Regulatory effects of four ginsenoside monomers in humoral immunity of systemic lupus erythematosus - Yu, Xin (Exp Ther Med, 2018)
Ginsenosides Rb1, Rh1, Rg1 and Rg3 are known as the main active components extracted from the roots of the Panax ginseng C.A. Meyer, and were reported to have immunoregulatory effects. Disruption of B-cell immune regulation during the pathogenesis of systemic lupus erythematosus (SLE) may lead to the production of large amounts of antibodies. The present study investigated the effects of the four ginsenoside monomers on B-cell immune regulation and observed that they inhibited the proliferation and secretion of B cells induced by LPS, caused an upregulation of the expression of apoptosis-associated proteins Fas/Fas ligand and caspase-3, the expression of FcγRIIB (CD32) as well as the proportion of inactive B cells (CD19(+)CD27(−)). These results indicate that Rb1, Rh1, Rg1 and Rg3 inhibit the humoral immunity of SLE, among which Rh1 exhibited the most obvious inhibitory effect.